A Novel Study on Natural Robotic Rehabilitation Exergames Using the Unaffected Arm of Stroke Patients - Mohamad Hoda; Yehya Hoda; Atif Alamri; Basim Hafidh; Abdulmotaleb El Saddik (International Journal of Distributed Sensor Networks, 2015)
We design and implement a low-cost rehabilitation glove to meet the needs of those patients who have paralysis in their affected hand. The novelty of this glove is that it is to be worn on the unaffected hand which acts as a natural robotic arm during the rehabilitation session. The glove is equipped with FSR sensors that measure the forces exerted by the affected hand on the unaffected hand. A virtual reality rehabilitation game is developed using Microsoft Kinect to facilitate the exercises and motivate the patients. The system is tested on three patients for six weeks. Objective measurements showed that patients have significantly improved over the study period. Moreover, the patients themselves gave positive feedback on the whole system; wearing the glove on the unaffected hand made their life easier and let them enjoy the rehabilitation sessions.